The Application of Educational Tourism in the Forest City of Tebet, South Jakarta - Irvan Akbar Kusuma; Silia Yuslim; Etty Indrawati (Journal of Synergy Landscape, 2022)
The Tebet city forest, located in the Tebet Barat Village, South Jakarta, is a green open space and is one of the urban forests in the city of Jakarta. The Tebet City Forest as a means of recreation and education is still not functioning correctly, so it is necessary to evaluate the existing facilities in the Tebet City Forest to realize educational tourism. The purpose of this study is to provide an overview of the state of the facilities in the Tebet City Forest, to provide alternative educational facilities that are suitable to be placed in the Tebet City Forest and to realize a landscape design that makes the Tebet City Forest an urban forest that facilitates educational tourism. This research uses a descriptive-analytical method. Through this method, researchers collect data through primary data and secondary data. The variables of the Tebet urban forest are cognitive, affective, and psychomotor. The results of this study indicate that facilities that can increase knowledge can be in the form of adding Indonesian plants, adding boards containing local names, Latin names, families, origins, and benefits for each tree, and providing community reading garden facilities. Facilities for protecting the environment include trash bins and signs for protecting the environment at every point of activity. Bus stops encourage people to use public transportation, provide bicycle rental and bicycle parking spaces, and provide open lawns and amphitheaters that can be used for various educational activities. Facilities that accommodate physical/physical activities include a children's playground, outdoor fitness, jogging track, multifunctional field, multifunctional plaza, amphitheater, and reflection area. It is necessary to develop and provide facilities that can support educational tourism. The results of this study can be implemented in a program that needs to be poured into the design of the site plan.